O papel do movimento espontâneo no desempenho da memória operacional em crianças com o Transtorno de Déficit de Atenção e Hiperatividade - TDAH - Simara Regina de Oliveira Ribeiro (2020)
Occurring in most cultures in about 5% of the child population, Attention Deficit Hyperactivity Disorder (ADHD) is the most frequent neurodevelopmental disorder. It presents symptomatic triad involving inattention, hyperactivity and impulsivity. To date, it does not have a biological marker, however, several neurostructural and neurofunctional changes are described. Different theoretical models seek to explain the mechanisms underlying ADHD, among them, there is a model that advocates the occurrence of a functional relationship between working memory (WM), seen as deficient in ADHD and spontaneous movement (SM), here associated with hyperactivity motor. In it, excess SM is understood as a compensatory mechanism that facilitates neurocognitive functioning in children with ADHD. This research aimed to investigate the role of SM in the performance of WM in children with ADHD. It used objective instruments of physiological analysis involving actigraphy, EEG and fNIRS as a resource, associated with school equipment called a stationary bicycle. The research was developed through two studies. In the first 25 children with ADHD were evaluated in order to verify the relationship between SM and cognitive effort, engagement and distraction during the performance of WM tests. In the second, 15 children with ADHD were evaluated in order to verify the relationship between SM and levels of cerebral hemodynamics of the prefrontal and motor cortex during the performance of WM tests and during the exhibition of children's animation trailers and excerpts from video lessons. In general, we can recognize through the results of this research that SM cannot be considered as a predictor of the performance of WM in children with ADHD, refuting assumptions of the adopted theoretical model, pointing out the non-occurrence of a function relationship between SM and WM.